Crystallographic structure determination of B10 mutants of Vitreoscilla hemoglobin: role of Tyr29 (B10) in the structure of the ligand‐binding site. Issue 3 (24th March 2013) - Ratakonda, Sireesha; Anand, Arvind; Dikshit, Kanak; Stark, Benjamin C.; Howard, Andrew J.
<x xml:space="preserve">Abstract</x> Site‐directed mutants of the gene encoding wild‐type Vitreoscilla hemoglobin were made that changed Tyr29 (B10) of the wild‐type Vitreoscilla hemoglobin (VHb) to either Phe or Ala. The wild‐type and the two mutant hemoglobins were expressed in Escherichia coli and purified to homogeneity. The binding of the two mutants to CO was essentially identical to that of wild‐type VHb as determined by CO‐difference spectra. Circular‐dichroism spectra also showed the two mutants to be essentially the same as wild‐type VHb regarding overall helicity. All three VHbs were crystallized and their structures were determined at resolutions of 1.7–1.9 Å, which are similar to that of the original wild‐type structure determination. The Tyr29Phe mutant has a structure that is essentially indistinguishable from that of the wild type. However, the structure of the Tyr29Ala mutant has significant differences from that of the wild type. In addition, for the Tyr29Ala mutant it was possible to determine the positions of most of the residues in the D region, which was disordered in the originally reported structure of wild‐type VHb as well as in the wild‐type VHb structure reported here. In the Tyr29Ala mutant, the five‐membered ring of proline E8 (Pro54) occupies the space occupied by the aromatic ring of Tyr29 in the wild‐type structure. These results are discussed in the context of the proposed role of Tyr29 in the structure of the oxygen‐binding pocket.